Citizen Participation and Service Delivery: A case of Communities in Rukungiri Municipality. - Jonacent, Tumusiime (Kabale University, 2020)
Citizen participation is very significant for service delivery since it ensures accountability, reduces corruption, and brings equity in resource allocation. The study was about citizen participation and service delivery while considering communities in Rukungiri Municipality a case study. It aimed at examining the relationship between citizen participation and service delivery in Rukungiri municipality under the following specific objectives; to establish the level of citizen participation in Rukungiri municipality, to establish the quality of service delivery to citizens in Rukungiri municipality and to determine the relationship between level of citizen participation and quality service delivery in Rukungiri municipality. The study adopted a cross sectional-descriptive study design with the population size being 2907households in Rukungiri municipality from which a sample of 352 household heads was selected. A questionnaire was administered to 323 household heads who were recruited using simple random sampling technique while researcher administered interviews were conducted with 29 local leaders using purposively sampled. Qualitative data was analyzed using descriptive statistics such as percentages and frequencies and in order to describe the relationship between the variables, Pearson product moment correlation index, and simple regression analysis were used. The study findings revealed that level of citizen participation in Rukungiri Municipality was medium, the quality of service delivery in Rukungiri Municipality was fair and that there is a substantial positive relationship between citizen participation and service delivery which accounts for 41.4% of the variability in quality of service delivery. The study recommended that Rukungiri municipal council and other district local governments should; improve citizen participation through involving them in planning and decision making process, project implementation and monitoring and evaluation, should put control systems to minimize corruption in service delivery, ensure accountability and equitable distribution of services and should involve citizens more since citizen participation improves service delivery and accounts for 41.4% of the variability in quality of service delivery.